2014
DOI: 10.1130/ges00986.1
|View full text |Cite
|
Sign up to set email alerts
|

Abandonment of Unaweep Canyon (1.4–0.8 Ma), western Colorado: Effects of stream capture and anomalously rapid Pleistocene river incision

Abstract: Cosmogenic-burial and U-series dating, identifi cation of fl uvial terraces and lacustrine deposits, and river profi le reconstructions show that capture of the GunnisonRiver by the Colorado River and abandonment of Unaweep Canyon (Colorado, USA) occurred between 1.4 and 0.8 Ma. This event led to a rapid pulse of incision unlike any documented in the Rocky Mountains. Following abandonment of Unaweep Canyon by the ancestral Gunnison River, a wave of incision propagated upvalley rapidly through Mancos Shale at r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 37 publications
3
37
1
Order By: Relevance
“…This is a 0.5 m.y. older than the burial age of the Cactus Park gravels (800 ± 240 ka, discussed herein; also see Aslan et al, 2014). Based on the evidence that the Gunnison River did not contribute to Cactus Park lake, whereas it sourced the western Unaweep lake, the improbability that the western Unaweep lake level could have been high enough to reach the top of the Cactus Park lake beds, and the considerable difference in apparent ages of the two lakes, we conclude that the two lakes were distinct and that the western Unaweep lake is older than the Cactus Park lake.…”
Section: Triangle Mesa Areamentioning
confidence: 80%
See 3 more Smart Citations
“…This is a 0.5 m.y. older than the burial age of the Cactus Park gravels (800 ± 240 ka, discussed herein; also see Aslan et al, 2014). Based on the evidence that the Gunnison River did not contribute to Cactus Park lake, whereas it sourced the western Unaweep lake, the improbability that the western Unaweep lake level could have been high enough to reach the top of the Cactus Park lake beds, and the considerable difference in apparent ages of the two lakes, we conclude that the two lakes were distinct and that the western Unaweep lake is older than the Cactus Park lake.…”
Section: Triangle Mesa Areamentioning
confidence: 80%
“…Our clast counts indicate that the gravel in the pit matches these values reasonably well, with 65% intermediate volcanic clasts, 14% metamorphic, 14% felsic on June 9, 2014 geosphere.gsapubs.org Downloaded from volcanic and granites, and 7% other rock types. The age distribution of detrital zircons is also similar to the modern Gunnison River, adding more evidence that these gravels are ancestral Gunnison River gravels (Aslan et al, 2014). Caskey (2008) also examined several outcrops of Cactus Park gravel, comparing the composition of Cactus Park gravel to that of the Colorado, Uncompahgre, and Gunnison Rivers, and also concluded that the Cactus Park gravel originated in the Gunnison River.…”
Section: Cactus Park Valleymentioning
confidence: 93%
See 2 more Smart Citations
“…The prevailing fl uvial hypothesis posits original canyon formation by the ancestral Gunnison River (Peale, 1877;Cater, 1966Cater, , 1970Sinnock, 1981), the ancestral Colorado River, or a combined Colorado-Gunnison (Gannett, 1882;Stokes, 1948;Shoemaker, 1954;Cater, 1955a;Hunt, 1956;Lohman, 1961Lohman, , 1981Steven , 2002;Aslan et al, 2008Aslan et al, , 2010Aslan et al, , 2014Hood, 2011;Hood et al, 2014). Some suggested that the Dolores River fl owed northeastward to carve Unaweep Canyon (Peale, 1877;Hunt, 1956).…”
Section: Unaweep Canyonmentioning
confidence: 99%